IMPERATIVES OF VOCATIONAL EDUCATION AND SUSTAINABLE DEVELOPMENT IN NIGERIA - Olayinka Phillip OGUNMOLA (EPRA International Journal of Research and Development (IJRD), 2023)
Sustainable development is only possible if there is a critical mass of skilled people as there is increased capital returns when the level of education goes higher and this will push the nation out of the middle income into high economy. Vocational Education (VE) play a pivotal role in the provision of skilled workforce needed for the country’s economic transformation.The investigation embraced the adopted for this study is a descriptive survey designThe study was carried out among adolescent making used of 120 students. Three hypothesis formulated, tested and used.The data were analyzed using inferential statistics of PearsonProduct Movement correlation (PPMC) and Regression Analysis was used to test the null hypotheses, significance will be taken at 0.05 level.The study found out that there was a positive significant relationship between technical knowledge andsustainable development in Ibadan Oyo State (r = .446**, N= 120, p<.05) among Adolescent in also result shows that there was a positive significant relationship between and vocational skills on sustainable development in Ibadan Oyo State (r = .484**, N= 120, p<.05) among Adolescent in Ibadan Oyo State and significant joint and relative of technical knowledge and vocational skills on sustainable development in Ibadan Oyo State. The study concluded thatLifelong learning is a self-motivated and voluntary pursuit of knowledge for professional or Vocational Education, it takes place throughout life and in many situations. Therefore, it recommended that There should be adequate emphasis on practical aspect of vocational education to enable the recipients acquire skills and reduce the over dependence on government paid jobs, Education and training should be made responsive to the changing needs of the globalized economy and there should be a widened access to education and training as this will reduce social and economic inequality.